2015
DOI: 10.1021/ic502609a
|View full text |Cite
|
Sign up to set email alerts
|

A Clean and General Strategy To Decorate a Titanium Metal–Organic Framework with Noble-Metal Nanoparticles for Versatile Photocatalytic Applications

Abstract: We demonstrate a facile and general approach for the fabrication of highly dispersed Au, Pd, and Pt nanoparticles (NPs) on MIL-125(Ti) without using extra reducing and capping agents. Noble-metal NP formation is directed by an in situ redox reaction between the reductive MIL-125(Ti) with Ti(3+) and oxidative metal salt precursors. The resulting composites function as efficient photocatalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(67 citation statements)
references
References 35 publications
2
61
0
3
Order By: Relevance
“…[94] Noble metal NPs formation is directed by an in situ redox reaction between the reductive MIL-125(Ti) with Ti 3+ and oxidative metal salt precursors (Scheme 7). [94] Noble metal NPs formation is directed by an in situ redox reaction between the reductive MIL-125(Ti) with Ti 3+ and oxidative metal salt precursors (Scheme 7).…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…[94] Noble metal NPs formation is directed by an in situ redox reaction between the reductive MIL-125(Ti) with Ti 3+ and oxidative metal salt precursors (Scheme 7). [94] Noble metal NPs formation is directed by an in situ redox reaction between the reductive MIL-125(Ti) with Ti 3+ and oxidative metal salt precursors (Scheme 7).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[94] TEM images revealed that the small Au,P d, and Pt NPs are homogeneously distributed on the MIL-125(Ti) with the average diameters of Au,P d, and Pt being 6, 3, and 3nm, respectively.MIL-125(Ti) showed aconversion of 18. [94] TEM images revealed that the small Au,P d, and Pt NPs are homogeneously distributed on the MIL-125(Ti) with the average diameters of Au,P d, and Pt being 6, 3, and 3nm, respectively.MIL-125(Ti) showed aconversion of 18.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…On exposure to UV radiation, the GO and Ag + are reduced to rGO and Ag 0 NPs in nitrogen atmosphere, simultaneously. This may be mainly due to the UV illumination of MIL‐125(Ti) initiating the formation of Ti 3+ by optically induced electron trapping at Ti 4+ sites . The Ag + and GO adsorbed onto MIL‐125(Ti) are reduced due to the strong reducing ability of Ti 3+ (−1.37 V versus SHE).…”
Section: Resultsmentioning
confidence: 99%
“…Shen et al . also decorated MIL‐125(Ti) with highly dispersed Au, Pd and Pt nanoparticles (NPs) via the photodeposition strategy . The presence of noble metal NPs as co‐catalysts plays an important role in enhancing the efficiency of H 2 production.…”
Section: Introductionmentioning
confidence: 99%
“…Over past years, composites of metal organic frameworks (MOFs) and inorganic nanomaterials have attracted much more attention for photocatalysis not only because of the significant charge separation by inducing charge carrier transfer at the interface of the composites, but also due to the porous structure and high specific surface areas of MOFs, which lead to high loading capability and avoiding the agglomeration of inorganic nanomaterials . To date, such inorganic nanomaterials mainly focus on SnO 2 , PbO, ZnO, g‐C 3 N 4 and TiO 2 .…”
Section: Introductionmentioning
confidence: 99%